2005
DOI: 10.1111/j.1745-7254.2005.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of atenolol and amlodipine for lowering and stabilizing blood pressure in 2K1C renovascular hypertensive rats1

Abstract: Aim: To test the synergistic effects of atenolol and amlodipine on lowering blood pressure (BP) and reducing blood pressure variability (BPV) in 2-kidney, one-clip (2K1C) renovascular hypertensive rats. Methods: Forty-eight 2K1C renovascular hypertensive rats were randomly divided into 6 groups. They were respectively given 0.8% carboxymethylcellulose sodium (control), atenolol (10.0 mg/kg), amlodipine (1.0 mg/kg), and combined atenolol and amlodipine (low dose: 5.0+0.5 mg/kg; intermediate dose: 10.0+1.0 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The right renal artery was isolated through a flank incision, and a silver clip (0.2 mm internal gap) was placed on the renal artery, as described previously [15]. Sham-operated rats that underwent the same surgical procedure except for placement of the renal artery clip served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…The right renal artery was isolated through a flank incision, and a silver clip (0.2 mm internal gap) was placed on the renal artery, as described previously [15]. Sham-operated rats that underwent the same surgical procedure except for placement of the renal artery clip served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…At cellular level, several changes in the energy metabolism, actin-myosin crossbridge cycle and protein expression were identified in renovascular hypertensive rats [131]. In addition, the paramount role of activation of the RAAS [73,150] and the sympathetic nervous system [32,270] has been thoroughly studied. In the one-kidney model, no compensatory increase in sodium and water excretion can occur, and hence, fluid volume is retained, which means this model is thus a sodium-fluid volume-dependent model.…”
Section: K1c Ratmentioning
confidence: 99%
“…Several works within our Department (Second Military Medical University, Shanghai, China) have demonstrated that there is significant synergism between atenolol and amlodipine in lowering and stabilizing blood pressure. For an acute setting, the synergistic effect is at its highest when the dose proportion of the 2 drugs is 10:1 in hypertensive rats [8,9] . A number of reports have shown that the combination therapy of antihypertension has overt effects on organ protection in hypertensive rats [10] .…”
Section: Introductionmentioning
confidence: 99%